An Integrated Project Delivery – Based Supply Chain Management for Modular Construction in the Philippines - Capuyan, Ghlenn Perry Lao (Journal of International Conference Proceedings, 2024)
This study explores the enhancement of Supply Chain Management (SCM) efficiency in the Philippines' modular construction sector through Integrated Project Delivery (IPD). It highlights the critical alignment of SCM success factors with IPD principles, emphasizing the importance of collaboration in modular construction projects. The application of IPD addresses challenges like high initial costs and skilled labor demands, offering a promising strategy for advancing construction methodologies in emerging markets. Quantitative analysis via surveys among modular construction professionals assesses IPD's impact on SCM efficiency, uncovering a positive correlation between IPD adoption and compliance with SCM success factors, particularly in larger organizations. This reveals the benefits of early collaboration and shared management practices. The research proposes a comprehensive framework tailored to the Philippine construction industry to optimize SCM efficiency by integrating modular construction with IPD principles. This strategy aims to tackle unique organizational and individual challenges, offering insights for improving SCM practices through IPD. The study paves the way for superior project delivery in developing economies and calls for future research into IPD and SCM risks, the influence of organizational structures, and the role of emerging technologies and cultural factors in modular construction. Keywords: Critical Success Factors, Implementation Framework, Integrated Project Delivery, Modular Construction, Supply Chain Management